2009
DOI: 10.1086/605844
|View full text |Cite
|
Sign up to set email alerts
|

Heritable Factors Play a Major Role in Determining Host Responses toWuchereria bancroftiInfection in an Isolated South Pacific Island Population

Abstract: These data provide evidence of a key role for genetic factors in determining the host response to filarial infections in humans and emphasize the complexity of the relationships among the host, parasite, and environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…1) was observed, further supporting the idea that an immunosuppressive cytokine profile and the different Mf loads in bancroftian filariasis patients may be caused by the immunogenetics of the host. It has already been suggested that factors related to the presence of the parasite itself, i.e., CFA and Mf levels, might be influenced by the host genetics [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) was observed, further supporting the idea that an immunosuppressive cytokine profile and the different Mf loads in bancroftian filariasis patients may be caused by the immunogenetics of the host. It has already been suggested that factors related to the presence of the parasite itself, i.e., CFA and Mf levels, might be influenced by the host genetics [12].…”
Section: Discussionmentioning
confidence: 99%
“…The exact genetic factors that lead to families having a greater incidence of filariasis and pathology are just now being elucidated, and include recent findings from our group that show that single nucleotide polymorphisms (SNPs) in the promoter region of vascular endothelial growth factor-A (VEGF-A) are associated with increased risk of developing hydrocele [11]. Furthermore, a recent study by Cuenco et al on the isolated Pacific Island of Mauke strongly demonstrated an association between host genetics in clinical and immunologic responses to filarial infection in a well-characterized island population [12].…”
Section: Introductionmentioning
confidence: 96%
“…Genetic factors have been also found to influence the levels of protective antibodies against helminths, as shown for the IgG levels to larval and adult worm antigens in humans infected by W. bancrofti [36]. The heritability of circulating antibody levels against helminths (particularly IgG 1 and IgG 2 ) ranges between 70 and 80 % depending upon time and isotype [39], and gene expression analyses have found that many genes differentially expressed between resistant and susceptible animals are indeed implicated in antibody synthesis [40].…”
Section: Immunogenetics Of the Ige Responses To Ascaris And Allergensmentioning
confidence: 99%
“…Individual predisposition to get infected by heavy or light worm loads is maintained in treatmentreinfection studies [32], and aggregates in families [33,34]. Epidemiological studies revealed than in addition to exposure and household determinants, genetic factors account for an important proportion of the variation in worm loads [35][36][37][38].…”
Section: Immunogenetics Of the Ige Responses To Ascaris And Allergensmentioning
confidence: 99%
“…The genetic makeup of animals and humans profoundly affects their susceptibility to helminth infections as well as the nature of their immune response (Williams-Blangero et al, 1999, 2002Cuenco et al, 2009). Nejsum et al (2009a) found that infection levels of the two most abundant gastrointestinal nematodes in pigs, i.e., the roundworm Ascaris suum and the whipworm Trichuris suis, had significant heritabilities, with 29-45% of the variation in A. suum worm counts and 32-73% of the variation in T. suis faecal egg counts explained by host genetics.…”
Section: Introductionmentioning
confidence: 99%